2016
DOI: 10.1155/2016/5794910
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Pulse Steroid Therapy and Bone Mineral Density in Patients with Multiple Sclerosis

Abstract: Multiple sclerosis (MS) has been associated with reduced bone mineral density (BMD). The purpose of this study was to determine the possible factors affecting BMD in patients with MS. We included consecutive 155 patients with MS and 90 age- and sex-matched control subjects. Patients with MS exhibited significantly lower T-scores and Z-scores in the femoral neck and trochanter compared to the controls. Ninety-four (61%) patients had reduced bone mass in either the lumbar spine or the femoral neck; of these, 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(55 reference statements)
0
5
2
Order By: Relevance
“…The studies investigating the effect of IVMP therapy on BMD in MS patients reported conflicting re- (20). However, in our study and some others reported no significant relationship between cumulative pulse CS dose and BMD (5,16,18). Similarly, Olson et al reported reduced BMD compared to a large cohort of MS patients in Denmark and an age-appropriate reference population, but they found no significant association between glucocorticoids (GC) dose (13).…”
Section: Discussioncontrasting
confidence: 70%
“…The studies investigating the effect of IVMP therapy on BMD in MS patients reported conflicting re- (20). However, in our study and some others reported no significant relationship between cumulative pulse CS dose and BMD (5,16,18). Similarly, Olson et al reported reduced BMD compared to a large cohort of MS patients in Denmark and an age-appropriate reference population, but they found no significant association between glucocorticoids (GC) dose (13).…”
Section: Discussioncontrasting
confidence: 70%
“…The relationship between BMD and iv. GCs in MS patients was confirmed by Tyblova et al [ 39 ], as opposed to other studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 74%
“…In the past, lower BMD values were observed in MS patients as compared to the control group [ 23 , 27 , 37 ]. A negative correlation between BMD and the EDSS was also reported [ 23 , 28 , 32 ], which was probably secondary to the impaired ability determining low BMD values. It was confirmed that one of the determinants of BMD is disease duration [ 28 ] and iv .…”
Section: Discussionmentioning
confidence: 88%
“…However, osteoporosis is more common in patients with MS compared with healthy populations; bone loss starts early during MS disease course, and increases as the disease progresses ( 55 , 56 ). Moreover, there is evidence showing that chronic use of glucocorticosteroids reduces bone formation and is a risk factor for osteoporotic fractures ( 57 ), although data from studies in MS patients are conflicting ( 58 60 ). In a case-control study examining the association between MS and likelihood of developing osteopenia or osteoporosis, a total of 91 men ( n = 45) and women ( n = 46) with MS (mean [SD] age: 52.0 [10.3] years) had a total body bone mineral density of 1.12 g/cm 2 and T-score of −0.6, indicating total bone density was not in the range of osteopenia or osteoporosis according to the World Health Organization classification.…”
Section: Clinical Assessment and Care Of Women With Msmentioning
confidence: 99%